2020
DOI: 10.3390/geosciences10120481
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of Long-Term Tsunami Hazards in Samoa Based on Sedimentary Signatures

Abstract: Investigating tsunamis and cyclones from depositional records enables an understanding of the long-term hazards to coastal communities. In Samoa, whilst a long-term record of tsunamis and cyclones spanning the last few millennia has been previously suggested based on preliminary sediment core/trench studies, a detailed assessment of the characteristics distinguishing these events has not been presented. This study reevaluates the depositional evidence available for Samoa and offers a more robust interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…The lesser known predecessor to the 2009 event, the 26 th June, 1917 UTC (local time in 1917 = UTC-11) earthquake and tsunami which originated in a proximal source region northwest of the 2009 epicentre (Figure 2), is arguably considered the largest earthquake to have occurred in this region in terms of magnitude (i.e., Mw 8.3 compared with Mw 8.1 for the 2009 earthquake sequence) [22][23][24]. However, the scale of impacts from the resulting tsunami appear to have paled in comparison with the devastation observed in the 2009 event (e.g., [25,26]). While anecdotal records indicate that the 1917 tsunami inundation had flooded several villages and caused damage to buildings and infrastructure (e.g., Satupaitea in southeast Savai'i and Lotofaga in southeast Upolu) [4,27,28], there are virtually no accounts of any casualties.…”
Section: Study Location and Historical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The lesser known predecessor to the 2009 event, the 26 th June, 1917 UTC (local time in 1917 = UTC-11) earthquake and tsunami which originated in a proximal source region northwest of the 2009 epicentre (Figure 2), is arguably considered the largest earthquake to have occurred in this region in terms of magnitude (i.e., Mw 8.3 compared with Mw 8.1 for the 2009 earthquake sequence) [22][23][24]. However, the scale of impacts from the resulting tsunami appear to have paled in comparison with the devastation observed in the 2009 event (e.g., [25,26]). While anecdotal records indicate that the 1917 tsunami inundation had flooded several villages and caused damage to buildings and infrastructure (e.g., Satupaitea in southeast Savai'i and Lotofaga in southeast Upolu) [4,27,28], there are virtually no accounts of any casualties.…”
Section: Study Location and Historical Contextmentioning
confidence: 99%
“…Runup observations derived from historical records of eyewitness accounts documented in [4,26,27], provided benchmarks to infer the extent of wave runup onto land. These information were digitized to help validate the tsunami runup modelling.…”
Section: Tide Gauge and Runup Observationsmentioning
confidence: 99%
“…Recent studies have revealed an apparent long-term local tsunami hazard in Samoa associated with the NTT source region [31]. Indeed, the most recent predecessor to the 2009 SPT was the 1917 Mw 8.3 Samoa-Tonga earthquake and tsunami, which is known to have inundated the southern coasts of Savaii and Upolu [28,32] (Figure 1).…”
Section: Study Location and Tsunami Hazard Contextmentioning
confidence: 99%
“…Indeed, the most recent predecessor to the 2009 SPT was the 1917 Mw 8.3 Samoa-Tonga earthquake and tsunami, which is known to have inundated the southern coasts of Savaii and Upolu [28,32] (Figure 1). Detailed historical records on the built environment's damage and loss of life from the 1917 event are scant (e.g., [28,31]). Available sedimentary and anecdotal evidence suggests that inundation was more geographically widespread than the 2009 SPT, extending west from Falealupo on Savaii eastward to Lalomanu on Upolu (e.g., [31]).…”
Section: Study Location and Tsunami Hazard Contextmentioning
confidence: 99%
See 1 more Smart Citation